Echoes of peasant voices: class struggle in the Ebro Valley (6th-7th Centuries) - Daflon, Eduardo Cardoso (Romanitas - Revista de Estudos Grecolatinos, 2026)
This text investigates the social transformations in the Ebro River valley between the 6th and 7th centuries through a cross-analysis of written documentation and archaeological data. It examines the relationship between the peasantry and the Visigothic aristocracy based on four variables: the organization of cities, the construction of fortifications, the processes of rural Christianization, and the reconfiguration of the countryside after the collapse of the Roman Empire. By highlighting peasant agency, the text challenges interpretations that reduce rural history to mere aristocratic domination, demonstrating that, despite the progressive expansion of seigneurial power, significant peasant communities maintained relative autonomy throughout a substantial part of the period. It thus advocates for a diachronic reading that understands class struggle in the Early Middle Ages as a dynamic process, marked by negotiations, resistance, and realignments between peasants and local aristocracies.